EVALUASI PENGGUNAAN QRIS MENGGUNAKAN MODEL UTAUT PADA ERA PERKEMBANGAN FINTECH - Ariyanto, Arif Setia Sandi; Yuttama, Faizal Rizky; Slamet, Slamet (Majalah Ilmiah METHODA, 2023)
Technological developments in the financial sector are growing very quickly, with the emergence of QRIS technology making non-cash transaction processes even easier. This platform can be used for almost all financial services. The author carried out this test to identify the influence between performance expectancy, social influence and facilitating conditions on behavioral intention to use QRIS in MSMEs in Banyumas Regency through Rumah BUMN Purwokerto using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. This test uses a data source totaling 99 respondents. Instrument validity and reliability tests were carried out using WarpPLS 8.0 software. The test results concluded that performance expectancy and facilitating conditions influenced the behavioral intention to use QRIS, while social influence did not influence the behavioral intention to use QRIS among MSMEs in Banyumas Regency.